Time-dependent solid-state molecular motion and colour tuning of host-guest systems by organic solvents - Yang, Yu-Dong; Ji, Xiaofan; Lu, Zhi-Hao; Yang, Jian; Gao, Chao; Zhang, Haoke; Tang, Ben Zhong; Sessler, Jonathan L.; Gong, Han-Yuan (Nature communications, 2020)
Host-guest complex solid state molecular motion is a critical but underexplored phenomenon. In principle, it can be used to control molecular machines that function in the solid state. Here we describe a solid state system that operates on the basis of complexation between an all-hydrocarbon macrocycle, D 4d -CDMB-8 , and perylene. Molecular motion in this solid state machine is induced by exposure to organic solvents or grinding and gives rise to different co-crystalline, mixed crystalline, or amorphous forms. Distinct time-dependent emissive responses are seen for different organic solvents as their respective vapours or when the solid forms are subject to grinding. This temporal feature allows the present D 4d -CDMB-8 ⊃perylene-based system to be used as a time-dependent, colour-based 4th dimension response element in pattern-based information codes. This work highlights how dynamic control over solid-state host-guest molecular motion may be used to induce a tuneable temporal response and provide materials with information storage capability. Host-guest solid state molecular motion is a critical but underexplored phenomenon which can be used to control molecular machines that function in the solid state. Here, the authors describe a solid state machine that shows solvent vapour- and mechanically-induced molecular motion that allows access to different crystalline and amorphous forms.